Answer:
Step-by-step explanation:
1). Given equation is,
2x² - 3x = 6
2x² - 3x - 6 = 0
To find the solutions of the equation we will use quadratic formula,
x = ![\frac{-b\pm\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
Substitute the values of a, b and c in the formula,
a = 2, b = -3 and c = -6
x = ![\frac{3\pm\sqrt{(-3)^2-4(2)(-6)}}{2(2)}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Cpm%5Csqrt%7B%28-3%29%5E2-4%282%29%28-6%29%7D%7D%7B2%282%29%7D)
x = ![\frac{3\pm\sqrt{9+48}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Cpm%5Csqrt%7B9%2B48%7D%7D%7B4%7D)
x = ![\frac{3\pm\sqrt{57}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Cpm%5Csqrt%7B57%7D%7D%7B4%7D)
x = ![\frac{3+\sqrt{57}}{4},\frac{3-\sqrt{57}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%2B%5Csqrt%7B57%7D%7D%7B4%7D%2C%5Cfrac%7B3-%5Csqrt%7B57%7D%7D%7B4%7D)
Therefore, there are two real solutions.
2). Given equation is,
x² + 1 = 2x
x² - 2x + 1 = 0
(x - 1)² = 0
x = 1
Therefore, there is one real solution of the equation.
3). 2x² + 3x + 2 = 0
By applying quadratic formula,
x = ![\frac{-b\pm\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
x = ![\frac{-3\pm\sqrt{3^2-4(2)(2)}}{2(2)}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%5Cpm%5Csqrt%7B3%5E2-4%282%29%282%29%7D%7D%7B2%282%29%7D)
x = ![\frac{-3\pm\sqrt{9-16}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%5Cpm%5Csqrt%7B9-16%7D%7D%7B4%7D)
x = ![\frac{-3\pm i\sqrt{7}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%5Cpm%20i%5Csqrt%7B7%7D%7D%7B4%7D)
x = ![\frac{-3+ i\sqrt{7}}{4},\frac{-3- i\sqrt{7}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%2B%20i%5Csqrt%7B7%7D%7D%7B4%7D%2C%5Cfrac%7B-3-%20i%5Csqrt%7B7%7D%7D%7B4%7D)
Therefore, there are two complex (non real) solutions.
Answer:
11
Step-by-step explanation:
since x>100, then 19-20x and 20-19x would obviously be negative and x-10 would be positive.
Therefore we have (20x-19)-(19x-20)-(x-10) = 20x-19-19x+20-x+10 = 11